Pengaruh Biaya Promosi Terhadap Peningkatan dana Tabungan Nasabah PT. Bank Rakyat Indonesia (Persero) Tbk. Unit Larangan Pamekasan - baihaki, ach (Unversitas Islam Madura, 2016)
The purpose of this study was to measure the magnitude of the effect of promotion costs to raise savings PT . Bank Rakyat Indonesia unit Larangan Pamekasan. PT . Bank Rakyat Indonesia ( Persero ) Tbk . is one state-owned bank , a financial institution whose business activities to collect funds from the public and run back the funds to the community and provide other banking services . This study uses a simple regression analysis is used to see how the dependent variable ( savings funds ) can be predicted by the independent variables ( cost of sale ) . The impact of the use of a simple regression analysis can be used to decide whether the rise and decline in the dependent variable can be done through raising / lowering the independent variable. Results of the study showed that the positive effect on the Promotion Cost Savings Fund Third Party Acquisition of BRI amounted to 45.8 % , the remaining 54.2 % were caused by other factors .